Jarak Tempuh Ergonomis Untuk Pedestrian yang Akan Beraktivitas - Mauluddin, Yusuf; Priatna, Rizal Ahmad (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 9 No 1 (2023): Volume 9 No 1 Tahun 2023, 2023)
Walking is a simple means in the transportation system. A pedestrian who walks regularly will nourish his body. The activity of walking to or from a place for activities such as work or college can be done every day. Sports activities that do not feel done, but are good for the body. The activity of walking to work must have sufficient distance so that when you arrive at work your body is still fresh and not tired. The purpose of this study is to determine the ergonomic mileage for pedestrians who will carry out activities such as workers or students. The method used in this study uses quantitative methods using descriptive statistics. Data collection was carried out with primary data which was carried out on a sample of students and office workers. The sample will be asked to walk on a treadmill assuming an unimpeded walk on a pedestrian path and at a relatively constant speed. To find out how far the ergonomic distance can be taken by the respondent in normal conditions or not feeling tired, the mileage is calculated until the heart rate reaches 125 beats/minute which is the lower limit of heart rate for heavy workload classification. The results showed that the average ergonomic distance that can be achieved is 744.69 meters for students and 522 meters for workers. Research also shows that the distance traveled is influenced by age, weight, and exercise habits. The results of this ergonomic mileage can be used for designing building layouts, parking space distances, pedestrian paths, setting the distance for resting seats on pedestrian paths, and so on.